Potensi Pertumbuhan Tanaman Jelutung Rawa di Kecamatan Jabiren Raya Kabupaten Pulang Pisau : Potential Growth of Swamp Jelutung Plants in Jabiren Raya District, Pulang Pisau Regency - Gaman, Sampang; Rotinsulu, Johanna Maria; Sukarna, Raden Mas; Penyang, Penyang; Nuwa, Nuwa (HUTAN TROPIKA, 2024)
The cultivation of swamp jelutong plants on peat swamp land has been widely practiced by communities in Central Kalimantan Province. However, jelutong cultivation efforts are prone to failure due to various factors such as land fires and other factors. The Indonesian government through the Ministry of Forestry in 2003-2005 carried out the Forest and Land Rehabilitation Movement, which involved planting unproductive land in state forest areas and community forests with local species such as jelutong, pulai, balangeran and other species. After almost 20 years of planting Jelutung, information related to the growth and sap potential of Jelutung swamp is not yet available. The purpose of the study was to analyze the potential growth of diameter and height of jelutong plants. This research was conducted for 3 months from October-December 2023. The location of the research was specifically carried out in Jabiren Raya Sub-district (Jelutung plantation of Mr. Margo) and (Jelutung plantation in Jabiren) Pulang Pisau District. The method used to study the dynamics of jelutong plant growth and sap potential was purposive sampling, by selecting and determining jelutong plants based on the age class of jelutong plants with a sampling intensity of ± 5% of the area, the measurement results were analyzed through correlation regression tests in the form of tables and graphs. The results of research conducted in 2 locations show the results of measurements of diameter and height growth of jelutong plants.